Does It Help? The Contribution of Wives' Ways of Giving Support to Their Veteran Husbands' Posttraumatic Stress Symptoms and Functional Impairment. Issue 6 (12th December 2018) - Dekel, Rachel; Siegel, Alana; Fridkin, Shimon; Svetlitzky, Vlad
Abstract: In this study, we aimed to understand female partners' ways of giving support to their male military veteran partners' adjustment. Specifically, we examined the direct and moderating contributions female partners' ways of giving support—active engagement, protective buffering, or overprotection—make on their male partners' posttraumatic stress symptoms (PTSS) and functional impairment. Our hypotheses were that (a) female partners' active engagement would be negatively correlated with male veterans' PTSS and positively associated with veterans' functioning, (b) female partners' protective buffering and overprotection would be positively correlated with veterans' PTSS and negatively associated with veterans' functioning, and (c) female partners' ways of giving support would moderate the association between their secondary PTSS and male partners' adjustment. Participants were 300 male Israeli veterans of the 2006 Israel–Lebanon War and their female partners, all of whom completed self‐report questionnaires. Active engagement did not contribute to female partners' or veterans' adjustment. In addition, whereas the correlations showed both female partners' protective buffering and overprotection were associated with male veterans' adjustment, the regression analysis showed only protective buffering made a direct, η 2 = .040 and .053, and moderating contribution to veterans' adjustment, η 2 = .019 and .016. Results revealed that when the level of protective buffering was high, female partners' secondary PTSS was associated more positively and strongly with veterans' PTSS than when protective buffering was low. The discussion reviews the complexity of giving support in couples when the veteran has PTSS.